PENGARUH PEMBERIAN TERAPI SEFT DAN MENDENGARKAN BACAAN AL-QUR’AN TERHADAP NYERI PASIEN POST OPERASI HERNIA - Alvin Abdillah (NHM PRESS, 2019)
Hernia postoperative pain is the sensation of pain felt by the patient's postoperative irritation caused by thestimulation of peripheral nerves along due to surgery. Fromthe results of the preliminary study in ward Irna A HospitalSyarifah Ambami Rato Ebu Bangkalan, it is found that thehigh incidence pain of postoperative hernia. The purpose ofthis study is to determine the effect before and after therapySEFT and listen Qur'an in patients with postoperativehernia in Irna ward A Hospital Syarifah Ambami Rato EbuBangkalan. The study design used